Anti-inflammatory effect of self-emulsifying delivery system containing Sonchus oleraceus Linn extract on streptozotocin-induced diabetic rats. (January 2020) - Chen, Lei; Lin, Xiujun; Xu, Xiaowei; Wang, Lihao; Teng, Hui; Cao, Hui
Abstract: Edible Sonchus oleraceus Linn is a medicinal plant with many bioactivities such as anti-diabetic activity and anti-inflammatory activity. However, the main bioactive components such as polyphenols in S. oleraceus Linn are poorly absorbed in gastrointestinal tract and rapidly metabolized. Thereby, a self-emulsifying delivery system containing S. oleraceus Linn extracts (SSEDDS) was introduced to evade these problems. Herein, the anti-inflammatory effect of SSEDDS on streptozotocin-induced diabetic rats was investigated. The plasma glucose level was increased and plasma insulin level was decreased in diabetic rats. The levels of NF-κB, TNF-α, and IL-6 in the liver were significantly improved in diabetic rats ( p  < 0.05). Conversely, daily fed diabetic rats with 100, 200 and 400 mg/kg/day of SSEDS and 1 mg/kg/day metformin for 4 weeks, significantly ( p  < 0.05) restored all the above mentioned parameters to near normal levels. The immuno-histochemical studies confirmed the anti-inflammatory effects of SSEDDS.